A Study on the Prevalence of Musculoskeletal Disorders among the Coalminers of Eastern Coalfields of India - Arunabha Bandyopadhyay; Samrat Dev; Somnath Gangopadhyay (Occupational Health and Safety Society of Nepal, 2012)
Background: Mining is an ancient occupation, long recognized as being arduous and liable to injury and disease. The lifecycle of mining consists of exploration, mine development, mine operation, decommissioning and land rehabilitation. Objective: To explore the prevalence characteristics and influence factors related to the development of work related musculoskeletal disorders of underground coalminers in Eastern Coalfield mines. Methods: In a cross-sectional study of 55 coalminers from Saatgram Project, Raniganj, Eastern Coalfields, modified Nordic Questionnaire was performed to assess the musculoskeletal disorders. Logistic regression analysis was performed to analyze the correlation between the occupational factors and their work related musculoskeletal disorders. Results: In this study 36 out of 55 miners (65.45%) complained about the development of musculoskeletal disorders at different body parts. The maximum pain was identified at lower back. The presence of lower back pain was observed among 58.18% of miners. The prevalence of pain in different body sites of the miners increased significantly with their ages. According to the present study, the repetitive operations and awkward postures were the risk factors for the development of work related musculoskeletal disorders in neck, shoulder and upper limbs; moreover, the repetitive operation of moving heavy substances and stooping postures continuously were related significantly - with the development of lower back pain at lower limbs due to the long standing awkward posture. Conclusion: It may be concluded from the above study that Eastern Coalfield miners are suffering from work related musculoskeletal disorders. This condition may be rectified by changing working postures or by implementation of ergonomically designed tools and machineries. DOI: http://dx.doi.org/10.3126/ijosh.v2i2.6596 International Journal of Occupational Safety and Health, Vol 2. No 2 (2012) 34-37